2020
DOI: 10.1039/d0tb01576h
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in the development on new liquid embolic agents for use in therapeutic embolisation

Abstract: Liquid formulations have a well-established role in therapeutic embolisation of blood vessels with the widespread use of cyanoacrylate glues, precipitating polymer suspensions, sclerosing agents and viscous emulsions of oil and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…Liquid embolic agents such as PHIL have several advantages over traditional coiling and particulate-based embolization techniques: they solidify when injected into the vasculature, providing a superior mould of their target area's geometry compared to coiling; the processes of solidification and occlusion are independent of the patient's physiology, allowing their use in patients with coagulopathies and patients receiving anti–coagulation treatment; and they are considered less likely to fragment and migrate than particulate-based embolic materials. Nevertheless, pulmonary migration remains a recognised but rare complication of embolization with liquid embolic materials [6] . PHIL is comprised of a polymer covalently bonded to an iodine compound (triiodophenol) [7] and so it appears radiopaque on X-ray and CT, presenting a diagnostic quandary if the patient's full past medical history is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid embolic agents such as PHIL have several advantages over traditional coiling and particulate-based embolization techniques: they solidify when injected into the vasculature, providing a superior mould of their target area's geometry compared to coiling; the processes of solidification and occlusion are independent of the patient's physiology, allowing their use in patients with coagulopathies and patients receiving anti–coagulation treatment; and they are considered less likely to fragment and migrate than particulate-based embolic materials. Nevertheless, pulmonary migration remains a recognised but rare complication of embolization with liquid embolic materials [6] . PHIL is comprised of a polymer covalently bonded to an iodine compound (triiodophenol) [7] and so it appears radiopaque on X-ray and CT, presenting a diagnostic quandary if the patient's full past medical history is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Another goal is the reduction of streak artefacts on radiographs and CT scans. Solvent-free formulations that gel upon contact with blood are of interest as means of avoiding the injection of potentially toxic solvents [ 68 ].…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…For completeness, the authors would like to mention that several agents, not discussed below, have been reported. 29 However, for this article, we have chosen to focus on those that are available in some markets but not all or are close to being approved for commercial use. Below we choose to divide the new products into three categories: polymerizing, precipitating, and phase transitioning.…”
Section: New Products In the Pipelinementioning
confidence: 99%
“…44 Furthermore, because Easyx does not gain radiopacity from tantalum powder, it does not require pre-shaking and would be delivered in a ready-to-use syringe. 29 45 While the device is not yet available for commercial use, several studies are currently underway and “EASYX-1: A multicenter Study on Safety and Efficacy of Easyx™ Liquid Embolization Agent Used in Five Separate Indications (EASYX-1)” has completed enrollment as of March 2020 according to clinicaltrials.gov. This promising device is therefore likely to be commercially available in the near future.…”
Section: Precipitating Agentsmentioning
confidence: 99%